Risk of Child Abuse and Its Predictors in Mothers with Children Under 5 Years Old - Homa Tohidi Noroodi; Leila Mirhadyan; Homa Mosaffa Khomami; Ehsan Kazemnezhad Leili (Guilan University of Medical Sciences, 2021)
Introduction: Child abuse as a public health problem has adverse consequences for children's physical and mental health. Even mothers may be responsible for child abuse, so it is essential to identify high-risk cases and take preventive measures. Objective: This study aimed to determine the potential risk of child abuse and its predictors of risk among mothers with children under 5 years old referred to comprehensive health service centers in Rasht City, Iran, in 2019. Materials and Methods: This is a cross-sectional study conducted on 450 mothers of children under 5 years old referred to the comprehensive health service centers in Rasht. The study data were collected by Adult-Adolescent Parenting Inventory form (AAPI-2 form A). The obtained data were analyzed using descriptive statistics, stepwise multiple linear regression, and the Friedman test to investigate the relationship between subscales. Results: The samples were mothers with a mean±SD age of 30.6±5.2 years. Mostly had diploma (41.78%), were housewife (79.33%) and all of them were married. The total mean±SD of score obtained for the child abuse risk was 3.18±0.56. Most mothers (87.31%) had moderate to severe level of child abuse risk. Based on multiple linear regression test, education (β=0.161, 95%CI; 0.076-0.247, P =0.001), being an employee (β=0.223, 95%CI; 0.059-0.387, P=0.008), family income (β=0.092, 95% CI; 0.006-0.179, P=0.037), spouse's education (β=0.128, 95% CI; 0.046-0.209, P=0.002), and addiction status of spouse (β=0.236, 95% CI; 0.006-0.466, P=0.044) were predictors of child abuse risk among the studied variables, respectively.  Conclusion: The results showed that most samples had a moderate risk of child abuse. It reveals the necessity to assess the attitudes of mothers about parenting, which predicts the potential of child abuse to some extent and can provide a basis of educational interventions for mothers to prevent child abuse.